2018
DOI: 10.1159/000491553
|View full text |Cite
|
Sign up to set email alerts
|

Time to Reset the Definition of Successful Revascularization in Endovascular Treatment of Acute Ischemic Stroke

Abstract: Background: A 2013 consensus statement recommended the use of the modified Treatment In Cerebral Ischemia (mTICI) scale to evaluate angiographic revascularization after endovascular treatment (EVT) of acute ischemic stroke due to its higher inter-rater agreement and capacity of clinical outcome prediction. The current definition of successful revascularization includes the achievement of grades mTICI 2b or 3. However, mTICI 2b grade encompasses a large heterogeneity of revascularization states, and prior studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this meta-analysis of acute stroke patients with anterior circulation large-artery occlusion, although the final successful reperfusion rate at the end of all endovascular procedures was significantly higher after first-line contact aspiration than after stent-retriever thrombectomy, the rate of final complete reperfusion and of functional independence did not differ between the two strategies. There is increasing evidence that complete reperfusion (mTICI ¼ 3) may more accurately predict good clinical outcome than the combined criteria of successful reperfusion (mTICI of 2b or 3), [46][47][48][49] and this may partly explain the findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis of acute stroke patients with anterior circulation large-artery occlusion, although the final successful reperfusion rate at the end of all endovascular procedures was significantly higher after first-line contact aspiration than after stent-retriever thrombectomy, the rate of final complete reperfusion and of functional independence did not differ between the two strategies. There is increasing evidence that complete reperfusion (mTICI ¼ 3) may more accurately predict good clinical outcome than the combined criteria of successful reperfusion (mTICI of 2b or 3), [46][47][48][49] and this may partly explain the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Successful reperfusion in endovascular therapy (EVT) for acute ischemic stroke is commonly defined as modified thrombolysis in cerebral infarction (mTICI) scores of 2b or 3 [1][2][3] . It has been shown that outcomes of patients with complete reperfusion (mTICI-3) are superior to those with incomplete reperfusion (mTICI-2b) [4][5][6][7][8][9][10][11][12][13][14][15][16] , and the importance of achieving mTICI-3 reperfusion is remarked. However, whether the superiority of mTICI-3 is retained in any patient subgroups has not been fully investigated.…”
mentioning
confidence: 99%
“…Inclusion criteria: (I) AIS with internal carotid artery/M1 middle cerebral artery segment thrombus; (II) received MTB treatment using the SR technique, followed by additional devices (e.g., ADAPT technique) at the operator’s discretion if failed; (III) all patients underwent CT imaging, including noncontrast CT (NCCT), CT angiography (CTA), and/or CT perfusion. Successful recanalization was defined as a Thrombolysis In Cerebral Infarction score 2b or 3 on the final digital subtracted angiography during MTB, as it represents a powerful predictor of treatment success and clinical outcome ( 19 ). Patients with unsatisfactory image quality, such as motion or metal artifacts, and incomplete clinical information were excluded.…”
Section: Methodsmentioning
confidence: 99%